Coronal tooth discoloration induced by regenerative endodontic treatment using different scaffolds and intracanal coronal barriers: a 6-month ex vivo study - Noushin Shokouhinejad; Hassan Razmi; Maryam Farbod; Marzieh Alikhasi; Josette Camilleri (Restorative Dentistry & Endodontics)
ObjectiveThe aim of this study was to evaluate discoloration of teeth undergoing regenerative endodontic procedures (REPs) using blood clot or platelet-rich fibrin (PRF) as the scaffolds and different calcium silicate-based materials as the intracanal coronal barriers in an ex vivo model.Materials and MethodsForty-eight bovine incisors were prepared and disinfected using 1 mg/mL double antibiotic paste (DAP). The specimens were then randomly divided into 2 groups (n = 24) according to the scaffolds (blood or PRF). After placement of scaffolds each group was divided into 2 subgroups (n = 12) according to the intracanal coronal barriers (ProRoot MTA or Biodentine). The pulp chamber walls were sealed with dentin bonding agent before placement of DAP and before placement of scaffolds. The color changes (∆E) were measured at different steps. The data were analyzed using 2-way analysis of variance.ResultsCoronal discoloration induced by DAP was not clinically perceptible (ΔE ≤ 3.3). Regarding the type of the scaffold, coronal discoloration was significantly higher in blood groups compared with PRF groups at the end of REP and after 1 month (p < 0.05). However, no significant difference was found between PRF and blood clot after 6 months (p > 0.05). Considering the type of intracanal coronal barrier, no significant difference existed between ProRoot MTA and Biodentine (p > 0.05).ConclusionsWith sealing the dentinal tubules of pulp chamber with a dentin bonding agent and application of DAP as an intracanal medicament, coronal color change of the teeth following the use of PRF and blood sealed with either ProRoot MTA or Biodentine was not different at 6-month follow-up.